Reconstructing Anamnesis in The Predisposition of The Directory Coverage of Prospective Librarians' Scholarly Works - Hascaryo Hascaryo (Universitas Terbuka, 2024)
Anamnesis is an interviewing activity conducted by interviewers with job applicants to obtain information about the applicant's educational, economic, social, and cultural background, as well as information about their experience, skills, and characteristics in order to avoid errors in making decisions about the required job position. Anamnesis uses interviewing techniques by asking structured and in-depth questions, including questions about the scientific work products of the job applicant, especially for librarian candidates. The scope of the directory should be able to be compiled in an interesting, in-depth, and varied manner through the suggestions of students or the guidance of scientific work advisers. The reality is that the student directory of scientific work authors still has a very limited thematic coverage area. The causes of this are among others, the students' lack of knowledge in disposing the theme of scientific work, which is about mobile libraries, archive preservation, human resources, library service quality, library effectiveness, library organization, library utilization strategies, library visitors, library roles, and library utilization. A wide thematic coverage can convince interviewers of the anamnesis activity to fulfill the standards or qualifications for librarians set by the workforce user. The directory of scientific work themes that have not yet been studied in the last 200 scientific works, include retrieval systems, indicative abstracts, informative abstracts, critical abstracts, mini abstracts, consecutive numeric, literary documentation, duplicators, electronic libraries, syndication, fumigation, historiography, interpolation, inversion, author catalogs, hybrid computers, classification, open services, monographs, news agencies, netiquette, public domain software, referral centers, retrospective, reviews, reproduction, roaming processes, quick references, alphabetical address filing systems, functional information systems, circulation, syllabification, secondary sources, telewriters, teleprocessing, bibliographic data, vertical recording, volume binding, web browsers, web hosting, working a beat, reference lists, message handling services, collection indexing, card control systems, zero access storage, subject headings, references, recordings, periodization, collection ordering, collection call numbers, reference collections, collection codes, library entrance counters, collection status, library modems, collection zones, web systems, equipment layouts, lexicon vocabulary, cataloging title catalogs, and archive restoration.